Using Complexity to Calibrate Legal Response to Covid-19 - Malcai, Ofer; Shur-Ofry, Michal (Frontiers in Physics, 2021)
The global effort to fight the Covid-19 pandemic triggered the adoption of unusual legal measures that restrict individual freedoms and raise acute legal questions. Yet, the conventional legal tools available to analyze those questions—including legal notions such as proportionality, equality, or the requisite levels of evidence—implicitly presume stable equilibria, and fail to capture the nonlinear properties of the pandemic. Because the pandemic diffuses in a complex system, using complexity theory can help align the law with its dynamics and produce a more effective legal response. We demonstrate how insights from complexity concerning temporal and spatial diffusion patterns, or the structure of the social network, can provide counter-intuitive answers to a series of pandemic-related legal questions pertaining to limitations of movement, privacy, business and religious freedoms, or prioritizing access to vaccines. This analysis could further inform legal policies aspiring to handle additional phenomena that diffuse in accordance with the principles of complexity.